Collaborative and Humanoid Robots - Hamilton Ortiz, Jesús; Kumar Vinjamuri, Ramana (IntechOpen, 2021)
Collaborative and Humanoid Robots guides readers through the fundamentals and state-of-the-art concepts and future expectations of robotics. It showcases interesting research topics on robots and cobots by researchers, industry practitioners, and academics. Divided into two sections on "Collaborative Robots" and "Humanoid Robots," this book includes surveys of recent publications that investigative the interaction between humanoid robots and humans; safe adaptive trajectory tracking control of robots; 3D printed, self-learning robots; robot trajectory, guidance, and control; social robots; Tiny Blind assistive humanoid robots; and more.